Investigation of the effects of binary hybrid nanofluids and different arrangements of corrugated tubes on thermal performance - Oflaz, Fatma (My University, 2025)
This research examined the effects of corrugation distance and nanofluid volume concentration on pressure drop, Nusselt number, and thermal performance in a circular tube. Binary nanofluid (MWCNT/Al?O?, 60:40) with volume fractions of 0.25%, 0.5%, and 1% was tested in corrugated tubes with distances of 10 mm, 20 mm, and 30 mm under constant heat flux (20 kW/m²) for Reynolds numbers between 10,000 and 40,000. 3D single-phase model was developed using ANSYS 19 with the standard k-? turbulence model and validated against equations from the literature. Results revealed that heat transfer improved with increasing Reynolds number, primarily due to elevated flow rates and intensified mixing induced by the corrugated surfaces. Compared to smooth tubes, the corrugated tubes exhibited higher Nusselt numbers, signifying better convective heat transfer performance. Nonetheless, this improvement was accompanied by increased friction factors and pressure drops, especially at shorter corrugation distances. Shorter corrugation distances intensified turbulence and mixing, enhancing heat transfer, while longer distances diminished turbulence, lowering the Nusselt number. The highest thermal performance, with a performance evaluation criterion of 1.27, was achieved at a corrugation distance of 10 mm and an MWCNT/Al?O? nanofluid concentration of 1%. For the same nanofluid concentration, the performance evaluation criterion was 1.24 at a corrugation distance of 20 mm and 1.21 at 30 mm, respectively.
Keywords: Heat transfer; Pressure drop; Binary nanofluid; Corrugated tube; Performance Evaluation Criteria